Sport injury prevention anatomy - Potach, D.; Meira, E. (Human Kinetics, 2023)
Develop a body that can withstand the rigorous pressures of competitive sport and physical activity! Sport Injury Prevention Anatomy offers you a detailed look into some of the most common sport injury conditions and the best exercises to help prevent their occurrence.